PERTUMBUHAN BIBIT CENGKEH (Syzygium aromaticum L.) PADA BERAGAM MEDIA PUPUK KANDANG - Johan Johan; Aiyen Tjoa; Ichwan Madauna (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The objective of this research was to determine the most effective type of manure for supporting the initial growth of clove seedlings. The study was conducted between October 2021 and February 2022 at Tadulako University's Faculty of Agriculture Screen House in Palu. Chicken, cow, goat, and sheep manure were each added to the planting medium at a ratio of 2:1 (v/v) and compared to non-manure treated media. Although the results indicated that none of the different types of manure had a significant impact on the growth of clove seedlings, cow manure showed some promise in terms of promoting clove height, leaf number, leaf area, and stem diameter.